التخطيط الاستراتيجي ودوره في تنمية وتطوير رأس المال البشري في أقسام الإعلام بالجهاز الإداري لسلطنة عمان: دراسة ميدانية - Badar bin Ahmed Al Balushi; Osama Kanaker (Universiti Sains Islam Malaysia, 2024)
This paper is a field study about strategic planning role in the development of human capital in the media departments at the administrative system of the Sultanate of Oman. The objective of the research is to identify the strategic planning foundations at the media departments and discuss the challenges that limit the effectiveness of the strategic planning practices. The quantitative approach were used, the questionnaire was designed, verified and arbitrated and distributed to a sample of (35) employees. Also distributed to a class sample of (304) information employees. The qualitative approach was also used in the interview with (29) directors of media departments. The frequency and percentage of each question were calculated in the questionnaire, the weighted average and the standard deviation were calculated. The findings revealed that, there is a defect in the administrative environment about the clarity of the strategic planning concept among the staff of the media departments, and a weakness in the implementation of planning functions, because of the challenges that prevent the activation of the role of planning. The recommendation; to use modern technology in strategic planning, and improve the staff development training programs.